Energi dan Saling Ketergantungan dalam Suatu Ekosistem Suatu Pengembangan Perangkat Pembelajaran Terpadu Tipe Connected di SLTP 21 Surabaya - Yenni, Ervi (Jurnal Pilar Sains, 2003)
The comprehension of learning sciences (IPA) connected type in senior high school (SLTP) 21 Surabayapurposes to describing as follows: (1) The activities of teacher and students, (2) The abilities of teacher onlearning management, (3) Students Respons to learning proses, (4) Evaluation student Result after attendinglearning Process (KBM) IPA type connected. Data observation had been done during 5-19 May 2001. Theresearch result showed teather activities in KBM increasing significantly, Student respons to KBM wasinterested in continuing the lessons. The proportion of answer-question is right encrising from 0.23 to 0.92.The conclusion of research is connected type.